Desenvolvimento de sistema de gerenciamento, supervisão, controle e aquisição de dados da microrrede universitária do campus do Pici - UFC - Ribeiro, José Cleison Cassiano (2020)
The recent trend of integration of distributed energy resources to the electricity distribution grids has led to the formation of microgrids (MR). MRs provide several benefits, being able to meet the growing demand, supply energy to remote areas and increase the reliability of supply due to unavailability of the main network or climatic catastrophes. For the safe and efficient operation of an MR, it is essential to develop and implement a supervisory and management system, whose basic functions are supervision, control and operation. This work presents the development and implementation of a data acquisition, supervision, control and management system for the MR installed in the Electrical Engineering Department of the Federal University of Ceará. The three-phase MR has three single-phase photovoltaic generation subsystems (SFV-1, SFV-2, SFV-3), which operate connected to the network, but have different operating characteristics: the SFV-1 is capable of operating in backup mode with the support of a battery system; SFV-2 has two sets (strings) of PV modules that can operate connected in series, just one string or both strings in parallel; and the SFV-3 can be connected to any of the three phases of the grid, according to the operator's decision. In this work, Elipse Power software was used for the development of the supervisory system, SoMachine for programming MR command equipment and SQL Server as a database, allowing collecting generation data from an energy analyzer installed at MR. Modbus TCP / IP protocol was used to communicate all the equipment used by the supervisory system. Tests were carried out to assess the performance of the management and SCADA functions in the supervision, control and operation of each PV subsystem, under different operating conditions of MR. The results of the tests confirmed the correct performance of the control devices for the operation of each MR subsystem. The graphic screens created in SCADA proved the proper record of the quantities collected in the database created for MR. Finally, the efficiency of the SCADA alarm center was also noted, as well as the alarm search screen, which showed the efficiency in the search for events and alarms that occurred in the MR within the selected time interval.